THE ROLE OF THE PAI TEACHER IN ESTABLISHING THE ISLAMIC CHARACTER OF STUDENTS - Nurul Qomariyah (Al-Fikru : Jurnal Pendidikan Dan Sains, 2022)
This research is motivated by a phenomenon of student delinquency which has recently become increasingly worrying, such as: brawls between students, promiscuity among adolescents, drug abuse and so on, from these problems teachers especially Islamic religious education teachers have a duty and role to improve behavior Islamic students. As for the focus of research in this case is to know how the role of Islamic Religious Education teachers in the formation of Islamic character.Data collected using observation, interviews, and documentation. As for the analysis, the researcher uses descriptive qualitative, namely in the form of descriptions and descriptions of the data collected as a whole about the actual situation.The results of this study indicate that Islamic religious education teachers play a role in shaping students' Islamic behavior. The role of the teacher as an educator in shaping Islamic behavior in students.Keywords: Role, PAI Teacher, Formation, Islamic Character